Workshop on leveraging the MGNREGA for resilient livelihoods for women - Narayanan, Sudha; Raghunathan, Kalyani; Ray, Soumyajit (International Food Policy Research Institute, 2024)
MGNREGA assets for value chains that promote resilience for women Lessons from other states. Presentation given September 2024.